Influência dos ativos intangíveis nas avaliações de analistas financeiros: uma investigação no mercado acionário brasileiro - Joyce Mariella Medeiros Cavalcanti (2018)
In the 21st century, intangible assets are the primary drivers of corporate value. However, despite their relevance, evaluating them is a complex task involving the debate about the responsibilities of Accounting and Finance. On the one hand, it is argued that Accounting should assess the intangible assets and fully disclose them in financial statements; on the other, it is argued that financial methodologies could help such evaluation since the asset values are uncertain. Therefore, Accounting should only highlight what is actually known about the value of intangible assets. In line with the second theoretical trend, it is assumed that financial analysts are agents capable of making these two perspectives converge. This becomes possible because of their role as information intermediaries in the Capital Market. Along these lines, the general objective of this thesis was to investigate how and to what extent intangible assets influence the evaluations of financial analysts who cover Brazilian companies listed in Brasil, Bolsa, Balcão (B3), from 2010 to 2016. To achieve the general objective, descriptive research was conducted, consisting of two stages of quantitative approaches. The first was carried out through content analysis and the second through panel data regression. Initially, the taxonomies of intangible assets were developed for content analysis by counting the repetition of the key terms pertaining the intangible assets mentioned in the financial analysts reports. The results revealed that analysts emphasize the structural intangible assets, particularly the corporate strategy and mission of companies. Next, we analyzed the influence of proxy variables on intangible assets on critical characteristics of financial analysts, such as coverage, error, and accuracy of the earnings per share forecasts. The results obtained through panel data analysis suggest the absence of statistically significant relationships between the variables studied. Thus, it is concluded that although financial analysts working in the Brazilian stock market make references to intangible assets in their reports which points to the relevance of these assets the difficulty of evaluating them, the scarcity of quality information about the development of such assets, and incentive problems discourage or even prevent their evaluations.